2011
DOI: 10.1029/2011tc002871
|View full text |Cite
|
Sign up to set email alerts
|

Controls of lithospheric structure and plate kinematics on rift architecture and evolution: An experimental modeling of the Baikal rift

Abstract: [1] Analog models investigate the evolution and architecture of the Baikal rift in relation to the rheology of the extending lithosphere and rift kinematics. The models focus on the development of the narrow, deep, and asymmetric basins composing Lake Baikal and reproduce the extension between the strong Siberian craton and the weaker Sayan-Baikal belt. Model results suggest that the presence of a near-vertical weak suture separating the cratonic keel from the mobile belt represents the more convenient rheolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 58 publications
(91 reference statements)
3
20
0
3
Order By: Relevance
“…Rifting in the Baikal rift started ca. 30 Ma, resulting in a series of narrow and elongated basins in the central and southwestern parts of the rift and narrow but shorter basins in the north (Delvaux et al, 1997;van der Beek, 1997;Corti et al, 2011). The orientation of the stress fi eld in the late Oligocene-Miocene that resulted in the onset of rifting was generally transtensional, with localized areas of transpression (Delvaux et al, 1997).…”
Section: Episodic Rifting On the Millions Of Years Time Scale: Observmentioning
confidence: 95%
See 1 more Smart Citation
“…Rifting in the Baikal rift started ca. 30 Ma, resulting in a series of narrow and elongated basins in the central and southwestern parts of the rift and narrow but shorter basins in the north (Delvaux et al, 1997;van der Beek, 1997;Corti et al, 2011). The orientation of the stress fi eld in the late Oligocene-Miocene that resulted in the onset of rifting was generally transtensional, with localized areas of transpression (Delvaux et al, 1997).…”
Section: Episodic Rifting On the Millions Of Years Time Scale: Observmentioning
confidence: 95%
“…Pure extension resulted in a change in fault kinematics in the central part of the Baikal rift, while the southern part underwent strike-slip motion. The change in stress orientation has been attributed to a change in the intraplate stress fi eld related to the India-Eurasia collision zone and subduction in the western Pacifi c (Corti et al, 2011), although some rotation may have been spe 500-11 1st pgs page 16 related to evolving basin linkage zones. Stress fi eld rotations also may have affected parts of the East African Rift System as rifting propagated along-axis, and Africa moved relative to the mantle upwelling (e.g., Strecker et al, 1990;Mortimer et al, 2007).…”
Section: Episodic Rifting On the Millions Of Years Time Scale: Observmentioning
confidence: 99%
“…In the Lake Baikal region, deformation is strongly localized at the craton border and characterized by a prominent asymmetry with the master fault on the craton side; conversely, to the northeast, a more diffuse deformation affects the weaker Sayan-Baikal belt, away from the craton border. Both numerical (Petit et al, 2008) and analog (Chemenda et al, 2002;Corti et al, 2011) models have suggested that the lateral variation in rheology of the lithosphere between the strong craton and the weaker belt together with the presence or absence of a weak suture in between may have strongly controlled the rift characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…This infl uence has been tested in a limited number of previous analogue models (Chemenda et al, 2002;Bonini et al, 2007;Corti et al, 2011); however, these works focused on the analysis of specifi c natural rift settings (Baikal rift, West Antarctic Rift System), and thus reproduced boundary conditions (e.g., plan-view geometry, thickness, and rheology on crustal and/or mantle layers) specifi c to the studied natural prototypes. In this paper, we expand and generalize these previous results by presenting analog models of rifting at craton margins.…”
Section: Introductionmentioning
confidence: 99%
“…При удалении на запад-юго-запад и северо-восток размеры области акти-визации увеличиваются до нескольких сотен ки-лометров, что совпадает с изменением конфигура-ции южной границы древней плиты. Влияние по-следней на развитие Байкальской рифтовой зоны не раз обсуждалось в предшествующих публикаци-ях [Logatchev, Florensov, 1978;Zorin et al, 2003;Petit, Déverchère, 2006;Seminsky, 2009;Corti et al, 2011]. Однако в этой работе наглядно показано влияние геометрии краевого шва на кинематику и ширину зоны локализации активных разломов.…”
Section: возраст активизации разломовunclassified